EFL Teachers' Perspectives on How AI Writing Tools Affect the Structure and Substance of Students' Writing - Nurseha, Ivan (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
The main objective of this research was to investigate the variety of Artificial Intelligence (AI) writing tools that are accessible and evaluate how teachers of English as a Foreign Language (EFL) perceive their impact on students' writing, specifically with regard to content and organization. The research was built within a case study framework, employing a qualitative method. Data describing the variety of AI writing tools and their effect on students' writing quality were gathered through semi-structured interviews. In order to shed light on the range of AI writing tools utilized in their classrooms, the study collected data from four EFL teachers throughout three different universities in Indonesia. Quillbot, WordTune, Jenni, ChatGPT, Paperpal, Copy.ai, and Essay Writer were among these apps. Furthermore, all of these educators concurred that the AI writing tools had a good impact on the caliber of writing produced by their students, especially with regard to topic and organization. The study's conclusions suggest that using AI writing tools can help improve the caliber of writing produced by EFL students. The limitations of this study were also addressed, along with suggestions for further research.